Radical and incremental creativity: associations with work performance and well-being. Issue 3 (23rd April 2020) - Zhang, Ying; Li, Jingjing; Song, Yahui; Gong, Zhenxing
Abstract : Purpose: Previous studies have focused on exploring the factors that influence employees' two distinct types of creativity, that is, radical and incremental creativity, while very little attention has been paid to the outcomes of creativity and how the two types of creativity interact within individuals. Design/methodology/approach: The present study addresses this issue by adopting both variable-centered (correlation) and person-centered (latent profile analysis) approaches for three samples of supervisor–employee dyads data from China ( n  = 159, 213 and 273). Findings: Using variable-centered analysis in sample 1, general creativity was positively associated with the four work performance dimensions, while there was no significant correlation between creativity and well-being. Using person-centered analysis, five very similar creativity profiles were found across samples 2 and 3 based on employees' radical and incremental creativity. These five classes differed in work performance dimensions and well-being, with classes characterized by a high level of incremental creativity profiles reporting a higher level of well-being and classes characterized by a high level of both incremental and radical creativity profiles reporting a higher level of the four work performance dimensions. Practical implications: Managers are suggested to focus on factors that could promote employees' incremental creativity if they want to have happier and highly performing employees, and they could also focus on factors that could aid employees who may experience costs when engaging in radical creative activities. Originality/value: The results of the present study contribute to uncover the potential outcomes related to employees' creativity by identifying distinct profiles of creativity types.